Analysis of Arabic Learning Methods: A Case Study at Madrasah Al-Yusufiyyah Al-Islamiyyah Chariyatham Suksa Foundation School, Thailand: Analisis Metode Pembelajaran Bahasa Arab: Studi Kasus Di Madrasah Al-Yusufiyyah Al-Islamiyyah Chariyatham Suksa Foundation School Thailand - Muhammad Ulil Abror; Daimah; Adi Wibowo; Ismail bin Muhammad (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Mastery of the Arabic language is a fundamental competence for students in Islamic educational institutions. However, at Madrasah Al-Yusufiyyah Al-Islamiyyah Chariyatham Suksa Foundation School in Thailand, some students still experience limitations in understanding texts and communicating in Arabic. This condition necessitates the implementation of more appropriate and contextual teaching methods. This study aims to analyse the Arabic language-teaching methods used in the school. Using a qualitative case study design, data were collected through classroom observations, interviews with Arabic language teachers, and the analysis of documents and learning materials. The findings indicate that the school employs an eclectic approach that combines the direct method, communicative approach, and grammar-translation method. This combination is suitable for students whose mother tongue is not Arabic. Its implementation has gradually improved students' abilities in text comprehension and communication. Thus, the eclectic method is effective and relevant for Arabic language instruction in multilingual contexts such as Thailand. Keywords: Al-Yusufiyyah Al-Islamiyyah Madrasah Thailand, Arabic Learning, Eclectic Approach, Learning Method.